ANALISIS FAKTOR DAN TINGKAT KEPUASAN DITINJAU DARI KUALITAS PRODUK DAN PELAYANAN PADA KONSUMEN SAYURAN ORGANIK DI LOTTE MART KOTA BANDUNG - Elly Rasmikayati; Bobby Rachmat Saefudin; Tuti Karyani; Kuswarini Kusno; Riky Rizkiansyah (Universitas Galuh Ciamis, 2020)
An increase in demand for organic vegetables encourages modern retailers to meet these demands so that the availability of quality organic vegetables must be sufficient so as not to disappoint consumers. Another thing that is often of concern to consumers in buying organic vegetables in modern retail is the quality of service in serving these organic vegetables given the higher price. Thus, the purpose of this paper is to analyze the satisfaction level of organic vegetables consumer on product quality and service quality at the Lotte Mart hypermarket in Bandung, which is one of the modern retailers that has long sold organic vegetables with various types of organic vegetables. The research design used is a quantitative design with a survey method. The sample size of the study was 42 respondents taken using the Systematic Random sampling technique. Data analysis technique used is a scoring technique dan factor analysis. The results showed that the level of consumer satisfaction on the quality of organic vegetables and the quality of service respectively were 75% and 77%, so it can be concluded that the consumers of organic vegetables were satisfied with the quality of vegetables and the quality of service in that modern retail. Based on the results of the factor analysis, it was found that the quality factor of organic vegetable products that had a significant effect on the level of consumer satisfaction was the presence of insect bites, attractive packaging and quality-appropriate price factors. While, service quality factors that significantly influence the level of customer satisfaction are factors of employee patience in serving, responses to complaints that are easily understood, speed and readiness to serve consumers and factors of employee knowledge about organic vegetables.